ChemInform Abstract: Studies on the Reaction of 16‐Dehydropregnenolone Acetate (16‐DPA) with m‐Chloroperbenzoic Acid. Issue 51 (17th December 2013) - Ghosh, Pranab; Subba, Raju
Abstract Epoxidation of 16‐DPA (I) with MCPBA on activated silica selectively leads to the 5, 6‐epoxy derivative (II), whereas the reaction of (I) with MCPBA in solution gives the diepoxy derivative (III) as an isomeric mixture.